Analyzing the Influence of the North Atlantic Ocean Variability on the Atlantic Meridional Mode on Decadal Time Scales - Sandro F. Veiga; Emanuel Giarolla; Paulo Nobre; Carlos A. Nobre (Atmosphere, 2019)
Important features of the Atlantic meridional mode (AMM) are not fully understood. We still do not know what determines its dominant decadal variability or the complex physical processes that sustain it. Using reanalysis datasets, we investigated the influence of the North Atlantic Ocean variability on the dominant decadal periodicity that characterizes the AMM. Statistical analyses demonstrated that the correlation between the sea surface temperature decadal variability in the Atlantic Ocean and the AMM time series characterizes the Atlantic multidecadal oscillation (AMO). This corroborates previous studies that demonstrated that the AMO precedes the AMM. A causal inference with a newly developed rigorous and quantitative causality analysis indicates that the AMO causes the AMM. To further understand the influence of the subsurface ocean on the AMM, the relationship between the ocean heat content (0–300 m) decadal variability and AMM was analyzed. The results show that although there is a significant zero-lag correlation between the ocean heat content in some regions of the North Atlantic (south of Greenland and in the eastern part of the North Atlantic) and the AMM, their cause-effect relationship on decadal time scales is unlikely. By correlating the AMO with the ocean heat content (0–300 m) decadal variability, the former precedes the latter; however, the causality analysis shows that the ocean heat content variability drives the AMO, corroborating several studies that point out the dominant role of the ocean heat transport convergence on AMO.